Spatial variability of soil electrical conductivity in an areawith coffee (Coffea arabica L.) fertilized via fertirrigation and traditional system - Conceição Rezende, Fátima; Barbiere Ribeiro, Victor; Fernandes Ávila, Leo; Alves de Faria, Manoel; Rogério de Mello, Carlos (Coffee Science - ISSN 1984-3909, 2011)
The aim of the present study was to evaluate the electrical conductivity (EC) soil profile in function of chemical fertilizer applied through fertigation and manual methods under the canopy. The crop was drip irrigated and irrigation was performed when the average voltage observed in “Watermark” sensors installed at 0.10 m depth reached 21 kPa. The irrigation depth was calculated using the average reading of soil water potential observed on the sensors installed at 0.10 and 0.30 m deep and the soil water retention curve. Under the tree canopy, in the drip bulb region, we installed 25 soil solution extractors at 0.10, 0.20, 0.30, 0.40 and 0.50 m deep and distant plant of 0, 10, 0.20, 0.30, 0.40 and 0.50 m. Sampling was conducted in irrigated and non irrigated plants during fertilization (October-March), for two years (2008/2009 and 2009/2010). The EC evaluations were performed 24 hours after fertilization, and between fertilizations. The results indicated that for irrigated and not irrigated plants, the EC of the soil showed spatial dependence. The application of fertilizer through water irrigation reduces EC of soil when compared to manual application. Doses and sources of fertilizer used do not promote soil salinization.